2011
DOI: 10.1093/humrep/der160
|View full text |Cite
|
Sign up to set email alerts
|

Testicular recovery after irradiation differs in prepubertal and pubertal non-human primates, and can be enhanced by autologous germ cell transplantation

Abstract: We conclude that irradiation before puberty has a severe detrimental effect on outgrowth of seminiferous tubules. But, within the seminiferous epithelium, spermatogenetic recovery occurs at a low rate with no detectable relation to the maturity of the epithelium at irradiation. We also show that autologous testis cell transplantation can enhance spermatogenesis, but only in isolated cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 17 publications
3
49
0
1
Order By: Relevance
“…In addition, for chemotherapy, alkylating agents and platinum analogues are highly gonadotoxic and lead to permanent azoospermia (Wallace et al, 2005). Furthermore, the pre-pubertal testis is not less vulnerable to the toxic effects of chemotherapy or radiotherapy compared with adult testis because of the constant turnover of early germ cells and the maturation process of Leydig cells, Sertoli cells and the other somatic cells of the different compartments during the infantile period (Jahnukainen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, for chemotherapy, alkylating agents and platinum analogues are highly gonadotoxic and lead to permanent azoospermia (Wallace et al, 2005). Furthermore, the pre-pubertal testis is not less vulnerable to the toxic effects of chemotherapy or radiotherapy compared with adult testis because of the constant turnover of early germ cells and the maturation process of Leydig cells, Sertoli cells and the other somatic cells of the different compartments during the infantile period (Jahnukainen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have shown the ability of human and non-human primates PSCs to differentiate into PGCs [3,17,29,44,45,55,56,62]. Although this cell lineage has the capability of restoring fertility in rodents, including primordial germ cells (PGCs) derived from mouse PSCs [6,20], SSCs remain the gold standard for colonizing cells which recapitulate spermatogenesis following transplantation [1,27]. Thus differentiating hPSCs into SSCs is an important step in the future ability for using patient-specific PSCs to restore fertility, as SSCs derived from PSCs can be transplanted into the sterilized testes to restore spermatogenesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our goal was to differentiate PSCs into spermatogonial stem cell (SSC)-like cells because this spermatogenic lineage has shown an exceptional ability to re-colonize sterilized testes and thus restore fertility in certain species including mice and non-human primates (NHPs) [1,22,27]. One advantage of this strategy is that there are established protocols for culturing and expanding rodent SSCs in vitro [28].…”
Section: Differentiation Of Human Pscs In Mouse Spermatogonialmentioning
confidence: 99%
“…Der Grad der Hodenschädigung sowie der temporä-ren oder sogar permanenten Einschrän-kung der Fertilität ist dosis-und altersabhängig. [23]. Dies ist ein Hinweis darauf, dass die Zahl der bei der Noxe im Hoden vorhandenen und anschließend überle-benden Stammzellen kritisch für das Regenerationspotenzial des Hodens ist.…”
Section: Grundlagen Der Männlichen Fertilitätsstörungunclassified